[P286] Study on semi-automatically evaluated micronucleus frequency changes in patients with prostate adenocarcinoma undergoing low and high dose rate brachytherapy. (August 2018) - Hulber, Timea; Kis, Enikő; Zsuzsa Kocsis, S.; Sáfrány, Géza; Pesznyák, Csilla
Abstract : Purpose: We compared the biological damaging effect of low and high dose rate brachytherapy (LDR and HDR) in healthy tissues of patients with prostate adenocarcinoma by following up the changes of DNA damage with cytokinesis-blocked micronucleus assay (CBMN) during and after the treatment. Methods: The CBMN assay was proven by literature to be good indicator of received dose during partial-body radiotherapy. The first blood samples were collected preceding the radiation therapy and the next ones in regular intervals after the seed insertion (LDR) or the end of treatment (HDR) (once every 3 month during the first year). The automatic analysis (scanning and image processing) was conducted by a dedicated totally automatized microscopic system. Results: We determined the MN frequency of 5 patients from each treatment group automatically and manually as well. We found that in order to ensure the reliability of the comparison of automatic scoring results an extra step has to be introduced for sample quality improvement. This way the tendency of MN frequency versus elapsed time became possible to be accurately identified and analysed for both brachytherapy techniques. Due to the relatively low whole-body equivalent dose, the best results were achieved with the user-supervised semi-automatic combined method which merges the advantages of the accuracy of manual revision and the rapidity of the automation. Conclusions: Although the signal is comparable with the order of changes, the automation-aided evaluation decreased the achieved uncertainty and made it possible to identify a definite and significant tendency in the change of MN frequency for LDR and HDR as well. Acknowledgment: This work has been carried out in the frame of VKSZ 14-1-2015-0021 Hungarian project supported by the National Research, Development and Innovation Fund.